Sighah Ikhtibarat al-'Arabiyyah fi Dui al-Ikhtibar al-Mutqn (TOAFL) - Ma'arif, Ahmad Syamsul (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract: Test of Arabic as a Foreign Language (TOAFL) is new standard of Arabic which is used by Indonesian religion ministry to measure the skill of Arabic students. TOAFL is also used by some Islamic State Universities in Indonesia in selecting the new students such as post graduate students. TOAFL is similar to TOEFL which consists of three section parts. Those are 1st Listening (Istima’), 2nd Grammar (Qowa’id), and 3rd Reading (Qiro’ah). The goal of this article are 1st to know the first history of TOAFL, 2nd to know the TOAFL test type, and 3rd to give specific recommendation for Indonesian religion ministry.Keywords: TOAFL, Islamic State Universities, Indonesian Religion Ministry